You overlooked the question at the bottom of the page that I tried 
unsuccessfully to work out. Brent supplied the answer but what I was looking 
for were the steps that lead up to the answer.   marty

  ----- Original Message ----- 
  From: Bruno Marchal 
  Sent: Friday, July 24, 2009 4:48 AM
  Subject: Re: Seven Step Series

      a^n * a^(-m) = a^(n-m)

      Again, verify this on simple example of your own.

      OK:  If a=10   and n=3 and   m=4  Following the formula above    "a^n * 
a^(-m)"   ,I get as the first half of the equation:

      10^3 * 10/4 =  1000 x 2.5=  2500   but for the second half   "a^(n-m)    
I get:

      10^(n-m)=  10^ -1=  10/1

      which of course makes no sense at all.     Where did I go wrong?



You received this message because you are subscribed to the Google Groups 
"Everything List" group.
To post to this group, send email to
To unsubscribe from this group, send email to
For more options, visit this group at

Reply via email to